2010
DOI: 10.1111/j.1365-3059.2009.02228.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical responses of coffee resistance against Meloidogyne exigua mediated by silicon

Abstract: Coffea arabica cultivars Catuaí 44 and IAPAR 59, susceptible and resistant, respectively, to the root knot nematode Meloidogyne exigua, were grown in pots containing Si-deficient soil amended with either calcium silicate (+Si) or calcium carbonate ()Si). There was an increase of 152 and 100%, respectively, in Si content of root tissue of cvs Catuaí 44 and IAPAR 59 in the +Si compared to the )Si treatment, but no significant difference between Si treatments for calcium content. Plants, assessed 150 days after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 25 publications
3
36
0
3
Order By: Relevance
“…Even so, reproduction of the nematode did not take place, since no eggs were found. It is thought that compounds connected to plant defense response are involved in this interaction, as reported by Silva et al (2010). These authors observed an increase in the activities of peroxidases, polyphenoloxidases and phenylalanine-ammonia-lyases as well as a higher concentration of lignin and phenolic compounds in the roots of the resistant coffee cultivar infected by M. exigua.…”
Section: Discussionsupporting
confidence: 57%
“…Even so, reproduction of the nematode did not take place, since no eggs were found. It is thought that compounds connected to plant defense response are involved in this interaction, as reported by Silva et al (2010). These authors observed an increase in the activities of peroxidases, polyphenoloxidases and phenylalanine-ammonia-lyases as well as a higher concentration of lignin and phenolic compounds in the roots of the resistant coffee cultivar infected by M. exigua.…”
Section: Discussionsupporting
confidence: 57%
“…Catuaí 44) crescidas em solução nutritiva contendo Si não apresentaram aumento no período de incubação e no período latente da ferrugem e nem mesmo redução no número de pústulas por folha, área pustular, expansão de pústulas e área abaixo da curva do progresso da ferrugem ou aumento na atividade de quitinases, β-1,3-glucanases e peroxidases. Porém, para a interação cafeeiro-Meloidogyne exigua, houve redução no número de galhas e de ovos do nematóide em associação com um aumento na concentração de lignina e na atividade de peroxidases, polifenoloxidases e fenilalanina amônia-liases no sistema radicular de plantas de cafeeiro da cultivar Catuaí 44 crescidas na presença de silicato de cálcio (Silva et al, 2010). Pereira et al (2009) relataram redução na severidade da ferrugem do cafeeiro com a aplicação foliar de silicato de potássio, porém não houve aumento na atividade de quitinases, ß-1,3-glucanases, peroxidases, polifenoloxidases, fenilalanina amônia-liases e lipoxigenases.…”
unclassified
“…As mentioned above (Section 4.2), silicon (Si) supplied to coffee plants was shown to decrease the number of rust lesions on leaves; Si also has an effect on resistance to nematodes. Silva et al (2010) found that a lower number of M. exigua galls and eggs occurred in the roots of coffee (C. arabica) plants that had been inoculated with the nematode and provided with Si, compared to control plants which were not supplied with Si.…”
Section: Nematodesmentioning
confidence: 99%